2008
DOI: 10.1590/s0066-782x2008001700006
|View full text |Cite
|
Sign up to set email alerts
|

Doutorado em cardiologia no Instituto do Coração da FMUSP, de 1994 a 2004: defesa e publicação

Abstract: A significant percentage of the dissertations were published, and in the group studied, publication took place within increasingly short times after their defense. This fact may be related to the success of the graduate commissions' policies and to the importance currently lent to debates on this theme, all of which contribute to improvement in the quality of graduate studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Cardiovascular surgery is generally considered a clean surgery, once the respiratory, digestive, and urinary tract are not involved during the surgical procedure and there is rarely a local infectious process [ 1 , 11 ] . Different studies have shown that HAI rates can range from 6% to 24%, depending on the characteristics of the services and patients, while the HAI rate in the cardiovascular surgery service of HC-UFPR is 22.6% [ 3 , 6 , 7 , 12 ] . Although within the expected percentage, HAI in our service is close to the upper limit of normality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardiovascular surgery is generally considered a clean surgery, once the respiratory, digestive, and urinary tract are not involved during the surgical procedure and there is rarely a local infectious process [ 1 , 11 ] . Different studies have shown that HAI rates can range from 6% to 24%, depending on the characteristics of the services and patients, while the HAI rate in the cardiovascular surgery service of HC-UFPR is 22.6% [ 3 , 6 , 7 , 12 ] . Although within the expected percentage, HAI in our service is close to the upper limit of normality.…”
Section: Discussionmentioning
confidence: 99%
“…The main classes of complications resulting from cardiovascular surgery are cardiac, pulmonary, renal, neurological, infectious, hematological, digestive and hydroelectrolytic [ 3 ] . Although cardiovascular surgery represents a type of operation with low infectious rate, infectious processes are usually among the main complications described [ 4 - 6 ] . The rates of HAI in cardiac surgery vary between 6 and 24% [ 3 , 6 , 7 ] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O formato de tese, muitas vezes disponível apenas nas bibliotecas das instituições, impedia sua divulgação mais ampla. No entanto, como apontam Marchini e Caramelli 4 , "a defesa de tese não é o fim de um processo, mas sim seu início, gerando conhecimento a ser divulgado, além de servir de alicerce para novos trabalhos". Fica reforçada, assim, a necessidade de moldarmos os trabalhos às exigências de cada periódico, e isso já se faz na elaboração do projeto de pesquisa.…”
Section: Discussionunclassified